The use of single dose of oral misoprostol (600µg) at home in management of first trimester miscarriages in El-Mukala, Yemen - Metwaly, Abo Bakr A.; Abbas, Ahmed M.; Al-Sakkaf, Maher (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: In the management of first trimester miscarriage, the use of oral misoprostol is beneficial for patients as it offers a more discrete and less invasive route for those women who find vaginal administration unacceptable. In spite of high incidence of side-effects from use of oral misoprostol women still found oral route satisfactory. Methods: This study was a prospective cohort study done at El-Mukala maternal and child hospital and Hadhramout maternal and child university hospital in the period between 1st October 2014 and 30th September 2015. All pregnant women (less than 14 weeks) who were diagnosed as an embryonic pregnancy or missed miscarriage were included in the study. Every patient received single dose of oral misoprostol 600 µg in half full stomach at home. The primary outcome measure was complete miscarriage rate. Results: One-hundred women were included in the study. The mean age of study participants was 26.25±4.08 years, the mean BMI was 27.35±3.6 while the mean parity was 2.6±1.5.Ten cases needed emergency surgical evacuation within the period of first 48 hours. Complete miscarriage had occurred in 75 cases, 65 of them in the first 48 hours. Fifteen cases presented by incomplete miscarriage after waiting for one week. They needed surgical evacuation at the end of 7 days due to still considerable intrauterine contents. Conclusions: In our closed community in El-Mukala, Yemen, the use of oral misoprostol in single dose of 600 µg at home as a method for termination of first-trimester miscarriage was effective (75%, success rate), tolerable regarding side effects, has the advantage of high confidentiality and privacy resulting in good satisfaction.